2019
DOI: 10.2507/ijsimm18(3)481
|View full text |Cite
|
Sign up to set email alerts
|

Urban Crowdsourced Last Mile Delivery: Mode of Transport Effects on Fleet Performance

Abstract: Minimizing last mile delivery costs is of paramount importance for all shipping companies that strive to stay competitive on the market. A potential solution to the problem is the use of crowdsourcinga model where individuals voluntarily take on a task proposed by another entity (e.g. a company). In this paper, we present the results of a comparison of performance for three types of crowdsourced delivery fleets likely to be used in an urban setting. The fleets differ in the mode of transport the couriers use: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Thus, the maximum willingness to work as crowd-shippers [21], expected pay value per delivery [31], and travel time tolerance issues [32] were studied. The potential readiness of people to be couriers was studied using survey methods [31,33], regression and correlation analysis [12,32] interviews [34], modeling [35][36][37]. Analysis of methods used in crowd shipping is presented in Table 1.…”
Section: Supply Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the maximum willingness to work as crowd-shippers [21], expected pay value per delivery [31], and travel time tolerance issues [32] were studied. The potential readiness of people to be couriers was studied using survey methods [31,33], regression and correlation analysis [12,32] interviews [34], modeling [35][36][37]. Analysis of methods used in crowd shipping is presented in Table 1.…”
Section: Supply Assessmentmentioning
confidence: 99%
“…When using interview and survey methods, frequently asked questions include willingness to become a courier [44,45], route [34], the amount of remuneration for work performed [37], the maximum deviation (both in time and distance) that the respondent would take for consent and rejection of the package [19,35].…”
Section: Supply Assessmentmentioning
confidence: 99%
“…Their study indicated that a mi xed model of crowdsourcing delivery and conventional logistics can save up to 62% of costs. Dupljanin et al (2019) used total delivered parcels and just-in-time delivery rates to quantify the performance of crowdsourcing delivery under different transpor t modes for m inim izing the transport cost. Arslan et al (2019) considered adopting a crowdsourcing delivery mode consolidating the dedicated vehicles of logistics businesses and ad hoc drivers' vehicles (crowdsourcing couriers' vehicles).…”
Section: Table 1 the Difference In Rural Last-mile Research Between Developing Countries And Developed Countriesmentioning
confidence: 99%
“…The last-mile delivery is considered to be the most expensive (Seghezzi et al, 2020) and an inefficient part of e-commerce logistics activities (Wang et al, 2016;Akeb et al, 2018;Dupljanin et al, 2019). It is the same for the last-mile of rural logistics and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, transhipment DC works with zero stock balance, and there are lower operational costs. The expenses for each delivery type are also highly dependent on pallet height [20]. In the case of DC order delivery -1.5 meters, and, in case of Store order delivery, the height of pallet is 1.2 meters (or 1.25 times lower).…”
Section: Shipping and Delivery Strategies For Serving Demand Pointsmentioning
confidence: 99%